Farmers Knowledge and Adoption of Aflatoxin Management Practices in Groundnut Farming (Indian Journal of Extension Education, 2011)
The groundnut (Arachis hypogaea L.) is a major oilseed crop of India. It has great potential for diversification for use as supplement food crop. The major impediment for diversification of groundnut is aflatoxin contamination. Aflatoxins are the toxic substances produced by the fungi Aspergillus flavus and A. parasiticus. The adoption of Aflatoxin Management Practices of Groundnut (AMPG) is very important for reducing aflatoxin contamination. In this study an ex post facto research design was used to understand the knowledge and adoption of aflatoxin management practices at farm level, identify the constraints faced by farmers in adoption of AMPG and seek the suggestions of farmers for improving the adoption of AMPG. The results revealed that most of the groundnut farmers does not possess adequate knowledge on AMPG and had not adopted the sowing, post sowing and post harvest AMPG. The most important constraint for adoption of AMPG was lack of premium price for aflatoxin free groundnut.